A doctoral student’s journey and experience in writing a research article through dialogic feedback: an autoethnographic self-reflection - Pahlevi, Muhammad Reza (Mell Baou Publisher, 2024)
One of the requirements of doctoral students is the ability to research and write scientific articles. Even though there has been a lot of research on article writing among doctoral students, it is still limited to using autoethnography designs. This paper reflects on a doctoral student’s experience in writing scientific articles during the intake of doctoral study. The design of this research is to use autoethnography which examines in depth the author's experience when writing articles during his doctoral studies. To collect data, this research uses reflective journals, photographs, and article document progress. Meanwhile, data analysis uses thematic analysis. The author's experience is operationalized by experiences, practices, and interesting episodes in the journey of writing articles presented meaningfully and in-depth. It is expected that this will have implications for becoming an alternative for writing scientific articles during doctoral studies or at other levels. The result of this study showed that dialogic feedback in writing an article promoted open-minded in accepting feedback that creates interactive discussion; stimulated problematizing dialog raises critical thinking in writing a research paper; and dialogic feedback enhances students’ motivation in refining a research article